The quality of life of patients with damage to knee joint cartilage - Czykieta, Izabela; Maj, Agnieszka Paula; Juzwiszyn, Jan Maciej; Czopor, Barbara (Journal of Education, Health and Sport, 2019)
Introduction. For many years, osteoarthritis (OA) had been considered a natural consequence of aging. According to statistics, it should be assumed that several million people affected by osteoarthritis live in Poland. The aim of the paper was to study the quality of life and the acceptance of the disease in patients with damage to knee joint cartilage.Material and methods. The study was conducted from January to December 2017 in the group of 100 people who were treated in the Clinical Department of Orthopedic and Traumatology of Locomotor System of Wroclaw Medical University. The research was conducted anonymously using the standard questionnaires WHOQoL-BREF. The inclusion criterium was a diagnosed injury to knee joint.Results. The mean evaluation of the quality of life carried out by the patients is 3.56 point (SD=0.9), which means that they assess their quality of life between good and average (not good, nor bad). The mean evaluation of the health status carried out by the patients equals 2.8 point (SD=1.1), which means that they assess their health status between unsatisfying and average (not satisfying, nor unsatisfying).Conclusions. The decreased perception of the quality of life in psychological and social domains was observed in relation to patients’ decision to undergo surgical treatment. These correlations are negative which means that the higher the pain intensity, the lower the quality of live in the above domains.Key words: chondromalacia, cartilage, the quality of life.